Belgien Transfer : Nordrhein-Westfalen. - Sint-Pietersabdij, Gent (Gent : Sint-Pietersabdij, 1993)
Roderburg, Johanna ; Sansoni, Andreas ; Devos, Danny ; Huyghe, Philip ; Crabeels, Cel ; Argüeso, Concha ; Tuerlinckx, Joëlle ; Geronnez, Alain ; Vergara, Angel ; Fauville, Daniel ; Rothemann, Gabriele ; Lanfer, Matthias ; Sery, Christian ; De Bruyckere, Berlinde ; etc.
Belgien Transfer : Nordrhein-Westfalen, Sint-Pietersabdij, Gent, 7 november - 19 december 1993
boek